A Review on Maternal Parenting, Child's Growth Stunting, and Oral Health - Abdulaziz, Rasyid; Suryanti, Netty; Setiawan, Arlette Suzy (European Journal of Dentistry, 2023)
Stunting has gained global attention as one of the most critical problems in public health. As the first and dominant figure in a child's life, the mother is responsible for determining the proper parenting behaviors to apply to maintain the child's physical health. Stunting is often associated with early childhood caries (ECC) and molar incisor hypomineralization, which can be manifested into each other through various mechanisms. Therefore, it is crucial to explore how far maternal parenting behaviors affect stunting and oral health. This study aims to determine which maternal parenting behaviors can affect stunting and oral health. A systematic search was used through PubMed and Google Scholar to search for published articles between 2011 and 2021. The articles analyze maternal parenting behaviors with stunting and poor oral health. Final analysis was used on 21 articles containing 18 cross-sectional studies, 2 cohort studies, and 1 randomized controlled trial. The result implied that the high prevalence of stunting and ECC is the combined result of prolonged breastfeeding practices (7 articles), poor complementary feeding practice (6 articles), high consumption of sugar (5 articles), and poor oral hygiene practices (5 articles). Maternal parenting styles in the aspect of fulfilling nutrition and maintaining oral health affect the occurrence of stunting and ECC in children.
Keywords: stunting; mother; feeding practice; oral health; early childhood caries